Analysis and Design of Regional Asset Leasing Management Information System in North Tapanuli Regency - Ardiles Sinaga; Frengki Simatupang; Istas Manalu; Hadi Sutanto Saragi (Politeknik Pertanian Negeri Samarinda, 2024)
Regional assets are something that has an essential role in the scope of local government because they have a complex value and are quite significant when compared to other components in the local government narrative. This requires local governments to be able to manage and utilize regional assets properly and correctly to increase Original Local Government Revenue in the region. Effective and efficient management of regional assets is one example of the management of the regional economy as shown in the Original Local Government Revenue. Improving the quality of regional asset management that is carried out professionally and modernly is a step taken to prioritize the principles of Good Governance. This research will discuss how to design a model for managing land assets of the North Tapanuli Regency local government that prioritizes the principles of Good Governance by utilizing information technology in the form of designing an information system that is expected to bring changes to the institutions that use it. The information system is expected to make the management of land assets spread across 15 sub-districts neater and more well-organized. In addition, the management of information related to asset leases can facilitate the reporting process and decision making. The purpose of this research is to design an information system as a reference for the Regional Finance and Asset Agency to develop an information system for managing regional assets and leasing regional assets by utilizing web-based and mobile technology. It is expected that through the information system designed in this research, the retribution payers can submit a Lease Application, upload the files of the Application Letter, and download the agreement letter through the application. Another technology that can be utilized in the information system to be built is the use of docker containers to run a lighter database and save time when storing all data related to the object of retribution, retribution payers, applications, lease agreement contracts, bills, and payments. This research also applies data storage technology that divides data into several separate units and then stored in one repository called object storage technology. This technology is used to store large data, create backup copies and archives, and store large amounts of images, graphics, video, or audio files.